(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Underground coal mining is known as one of the major sources of methane emissions which mainly occurs after underground coal extraction. Rock strata in-situ methane can potentially be the most significant hazard in coal mining operations. To prevent or minimize the risks of methane emissions, methane drainage approaches have been adopted by coal mines. Rock mass methane drainage is the most efficient and effective approach toward controlling methane hazards as it prevents and reduces the frequency of methane emissions, outflows into the working area and sudden outbursts of methane and rocks. The method includes drilling boreholes from the tailgate side to the unstressed zone in the roof and floor strata above and below a working coal seam. The coal seam gas content in Tabas Parvadeh I is estimated to be about 16 m3/t, which is relatively high. Based on exploration data, five distinct coal seams have been identified (B1, B2, C1, C2 and D) at the coal deposit and currently C1 is being worked. Considering the high value of C1 gas content and surrounding rocks, the Methane Drainage System (MDS) has been utilized for gas drainage. This paper tries to determine the desorption area which is essential and helpful for the selection of an effective drilling pattern into the adjacent coal seams. In this study, the methane drainage zone in the E4 panel of the Tabas coal mine was calculated using experimental equations and a drainage borehole pattern was determined.